Correlation Between Nutritional Status, Cognitive Function and Daytime Sleepiness of Schoolchildren in Terengganu, Malaysia - Rosli, Nurul Husna; Ali, Asma'; Kamarudin, Khairil Shazmin; Hamzah, Yusnita; Yusof, Hayati Mohd (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2021)
This cross-sectional study aimed to determine the correlation between nutritional status, cognitive function and daytime sleepiness of schoolchildren in Kuala Nerus, Terengganu. It involved 85 schoolchildren aged 9 to 12 years. Nutritional status was determined through anthropometric measurements, biochemical analyses for hemoglobin, urinalysis and urinary iodine concentration (UIC). While cognitive performance was tested using Raven’s Colored Progressive Matrices (R-CPM). The daytime sleepiness of the respondents was assessed using the Pediatric Daytime Sleepiness Scale (PDSS). It was found that 16.5% of the respondents were stunted while 4.7%, 12.9% and 17.7% were obese, overweight and wasted, respectively. In addition, 37.7% of the respondents were anemic and the median UIC was 177.0 µg/l, which was categorized as normal for children. The majority (37.6%) of the respondents had an average cognitive level. Furthermore, the mean for daytime sleepiness based on PDSS score for overall respondents was categorized under an average level that was 14.1 score. In the present research, results found that all of the factors examined in this study were not correlated with respondents’ cognitive function. As the majority of the children had average to low levels of cognitive functions, it is recommended to investigate further factors associated with cognitive functions and, subsequently, to design and deliver appropriate intervention.